ANALISIS VISUAL DALAM BRAND EQUITY PADA IKLAN UNIQLO LIVE LIFE IN FLANNEL - Hironimus Hari Kurniawan; Nicholaus Wayong Kabelen (UNIVERSITAS PGRI MADIUN, 2025)
This study analyzes Uniqlo's Live Life in Flannel advertisement using a semiotic approach to understand the visual and audio symbols employed and their impact on Uniqlos brand equity. This qualitative research utilizes video advertisement analysis to identify key elements such as color, visual narration, and audio composition that build a positive perception of Uniqlo's flannel products. The study also includes interviews with consumers who interact with Uniqlo's flannel products at its Surabaya store to gain further insights into their perceptions of product quality and brand image.The analysis results show that the Live Life in Flannel advertisement successfully creates strong associations between Uniqlos flannel products and symbols of friendship, comfort, and confidence. These symbols effectively shape brand awareness and brand associations in consumers' minds, reinforcing the perceived quality of Uniqlo's flannel products. Thus, this study highlights the importance of semiotic analysis in understanding the role of visual and audio elements in strengthening brand image and provides insights into how Uniqlo can leverage visual strategies to enhance its brand equity in a competitive market